Balancing The Principles of Non-Refoulment and National Security in The Protection of Refugee Rights: A Legal and Policy Analysis of Refugee Handling in Australia - Putri, Ria Wierma; Yunita Maya Putri; Ernawati, Ninin; Muhammad Havez; Febriyani Sabatira (Magister of Law, Faculty of Law, University of Mataram, 2024)
This study examines the delicate balance between the principle of non-refoulement and national security in protecting refugee rights, focusing on Australia’s approach to handling refugees. Non-refoulement, a fundamental principle of international refugee law, prohibits the forced return of individuals to countries where they may face persecution. However, ensuring national security while upholding refugee rights poses challenges, particularly in the face of global migration crises and security concerns. Through a case study of Australia’s refugee policies and practices, this research explores the complexities of navigating between these principles, considering legal frameworks, policy implications, humanitarian considerations, and the impact on refugee lives. The findings contribute to understanding the intricate dynamics of balancing humanitarian obligations with national security imperatives in refugee protection efforts. The findings of this research suggest that no balancing act can be justified by international law. Turn-back measures cannot be used to balance Australia’s international obligations to protect refugees. This will lead to violations of the human rights of asylum seekers who will be returned. The act of turning back is hazardous and has the potential to bring threats and persecution to asylum seekers who are returned to their country of arrival, country of origin, or third countries.